The Global Economy and Democracy: The Tuna-Dolphin Controversy Revisited - Bonanno , Alessandro; H. Constance, Douglas (The International Journal of Sociology of Agriculture and Food, 2021)
The paper investigates the limits and possibilities of democracy in the context of the globalization of the economy and society. Employing the case of the tuna-dolphin controversy, it is argued that though democratic spaces are available, the boundaries of discourses on democracy are shrinking. The movement which was able to establish legislation and procedures which prevented corporate exploitation of the environment is now divided, and existing pro-environment legislation is under attack. Indeed, TNCs have been able to establish a hegemonic project which drew support from segments of the environmental and labor movements. The paper reviews recent events which testify to the erosion of pro-environmental discourses and the shifting of alliances and solidarities around pro-TNC projects. The paper concludes with an analysis of the implications that these recent events have in regard to democracy in contemporary global capitalism. In particular, it is maintained that despite the powerful position of TNCs, they are still subject to contradictions and vulnerabilities which can be exploited by alternative movements.